Wanita Saat Ini, Antara Karier Dan Keluarga - Dompas, Saartje Laoh (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
Current statistic demographic of career women showed the rising figures that slowly shifted man domination on workplaces. The equality on education, training and self-development iduced women to do some works that never done before. It did not gradually change the women’s roles in the home – affairs, but it was a preference. This paper is the general descriptive explanation on the career – family preference among the women. Some epirical studies explained some combinations of preference choices between careers – family. Furthermore, on the estabilished corporate culture, there were some barruers on women’s participation, mainly corporate and informal barriers. These women’s barriers relative to male managers could explained an earlier career plateau of women workers. Finally, the conclusion is that personal orientations and perceived on work environments are important factors to the choices of the wise career – famili preference.